2009
DOI: 10.1002/bdrb.20179
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of interferon alpha‐2b and pegylated interferon alpha‐2b on menstrual cycles and ovarian hormones in cynomolgus monkeys

Abstract: Administration of hr-IFNalpha2b or PEG-hr-IFNalpha2b at high doses to cynomolgus monkeys resulted in similar effects on menstrual cycles, estradiol and progesterone profiles, and exhibited evidence of reversibility upon cessation of dosing. These results suggest that the previously observed high-dose IFNalpha-related effects on the maintenance of pregnancy in monkeys are likely the result of altered ovarian function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…They concluded that administration of both products at high doses resulted in similar effects on menstrual cycles, estradiol, and progesterone profiles, and that the previously observed highdose interferon-α effects on the maintenance of pregnancy in monkeys are likely the result of altered ovarian function [19].…”
Section: Reproductive/developmental Toxicitymentioning
confidence: 97%
“…They concluded that administration of both products at high doses resulted in similar effects on menstrual cycles, estradiol, and progesterone profiles, and that the previously observed highdose interferon-α effects on the maintenance of pregnancy in monkeys are likely the result of altered ovarian function [19].…”
Section: Reproductive/developmental Toxicitymentioning
confidence: 97%
“…Irregularities in the cynomolgus macaque ovarian cycle can predict impaired fertility in humans (Kolstad et al 1999; Jensen et al 1999; Small et al 2006; Brodin et al 2008). Test article–related prolongation of the ovarian cycle is not uncommon and is known for particular classes of test articles such as alpha2-interferons or inhibitors of epidermal growth factor signaling (Enright et al 2009; Bussiere et al 2013). The ovarian cycle duration might be secondarily affected by general toxicity of a test article, but systematic analyses in this direction have not been performed so far (Williams et al 2001; Williams, Berga, and Cameron 2007).…”
Section: How To Assess Female Fertility In Long-tailed Macaquesmentioning
confidence: 99%